Heart Systolic/Diastolic Variability and Heart Vibration Variability: Novel Indicators for Cardiac Function Assessment Based on Seismocardiography - Li, Yitang; Yu, Jianyun; Zhu, Xiaoli; Wang, Haoyue; Zhang, Zihan; Li, Jiangtao (International Conference on Bio-engineering for Smart Technologies (Online), 2025)
Seismocardiography (SCG) provides unique insights into cardiac mechanical function by recording chest wall vibrations, offering information beyond the electrical activity captured by electrocardiography (ECG). While heart rate variability (HRV) is widely used for autonomic assessment, it does not directly reflect mechanical function. This study introduces three novel SCG-derived indicators: heart vibration variability (HVV), heart systolic variability (HSV), and heart diastolic variability (HDV), which quantify beat-to-beat fluctuations in cardiac mechanics. Our findings reveal significant differences between healthy subjects and cardiac patients. This approach supplements traditional HRV by providing cardiac mechanical vibration variability, addressing the insensitivity of ECG in diagnosing valvular heart disease and structural heart disease.